EKSPLORASI PENGALAMAN PENGGUNAAN MEDIA AUGMENTED REALITY (AR) BERBASIS SMARTPHONE DALAM MENINGKATKAN KREATIVITAS SISWA SMA PADA MATA PELAJARAN PENDIDIKAN JASMANI DAN OLAHRAGA DI SMAN 9 KABUPATEN JENEPONTO - Dwi Nur Andini Putri; Kaharuddin, Irmawati Thahir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Smartphone-based Augmented Reality (AR) media is a technology that combines the real and virtual worlds interactively to support the learning process. This study aims to explore students' experiences in using smartphone-based AR media in Physical Education, Sports, and Health (PJOK) learning, and its impact on increasing student creativity at SMAN 9 Jeneponto Regency. This study uses a descriptive qualitative approach with a phenomenological method. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The selection of informants was carried out purposively, namely by selecting grade X students at SMAN 9 Jeneponto Regency who were considered to have relevant experience and understanding related to the use of smartphone-based Augmented Reality media in learning. The results of the study showed that the use of Augmented Reality (AR) media provides a more interesting, interactive, and enjoyable learning experience for students. This media is also able to encourage students to think more creatively in understanding and practicing sports learning materials. However, there are several technical obstacles faced, such as limited access to applications and unstable network connections. However, overall, AR media has significant potential in improving the quality of PJOK learning, especially in terms of active involvement and development of student creativity.